2022
DOI: 10.1021/acsanm.2c04089
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Quantum Dots for Fluorescence Turn-Off Detection of the Clodinafop Pesticide in Food Samples via Liquid–Liquid Microextraction

Abstract: Herein, red fluorescent CsPbI 3 perovskite quantum dots (PQDs) are successfully synthesized by a one-step reaction via a microwave irradiation method. The as-fabricated CsPbI 3 PQDs displayed a strong emission intensity at 686 nm when applied with a λ Ex of 350 nm. The as-synthesized CsPbI 3 PQDs were dispersed in hexane, and the quantum yield of CsPbI 3 PQDs was 27%. The CsPbI 3 PQDs were successfully integrated with liquid−liquid microextraction for the analysis of the clodinafop pesticide by fluorescence sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…93,94 The complicated cereal matrix interference in the use of perovskite nanocrystal-based biosensors could be avoided by organic solvent extraction of pesticides. 95 Clodinafop, an aryloxyphenoxy-propionate herbicide, has been extensively utilized to avoid the damage of annual grasses to cereal production. 96,97 To realize the rapid detection of clodinafop in rice, Vajubhai et al reported a fluorescent quenching biosensor to rapidly detect clodinafop based on CsPbI 3 PQDs that showed high emission intensity at 686 nm.…”
Section: Cereal Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…93,94 The complicated cereal matrix interference in the use of perovskite nanocrystal-based biosensors could be avoided by organic solvent extraction of pesticides. 95 Clodinafop, an aryloxyphenoxy-propionate herbicide, has been extensively utilized to avoid the damage of annual grasses to cereal production. 96,97 To realize the rapid detection of clodinafop in rice, Vajubhai et al reported a fluorescent quenching biosensor to rapidly detect clodinafop based on CsPbI 3 PQDs that showed high emission intensity at 686 nm.…”
Section: Cereal Productsmentioning
confidence: 99%
“…105 Besides, the fluorescent biosensor fabricated by Vajubhai et al have also been utilized for the detection of clodinafop in apple juice and tomato juice and has obtained good recoveries ranging from 97.13% to 100.66%. 95 Patulin, a poisonous mycotoxin produced by Penicillium, mainly contaminated fruits and their processed products and thus threatened human health though the food chain. 106 To monitor patulin in apples, Leng et al synthesized CsPbBr 3 perovskite QDs (CQ) with superior recognition and distinctive optical performance as luminogens and coupled them with MIP technology to construct PAT-recognized fluorescent nanoprobes.…”
Section: Cereal Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In addition, SDME technique is ideally suited for coupling with fluorescence spectroscopy because the solvent used in SDME is transparent in the visible region and does not interfere with direct visual readout and spectral analysis. 27,28 In recent years, the integration of liquid-phase microextraction with noninstrumental optical detection has been reported. However, the attention was concentrated mainly on the direct detection of the analyte to be assayed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Single-drop microextraction (SDME) is an eco-friendly and effective sample pretreatment technique, in which a microdroplet of organic solvent adheres to the tip of a microsyringe needle. Due to its minimum solvent consumption with a high sample-to-extractant phase ratio, SDME has been widely used in the fields of environmental monitoring, food quality control, and biological analysis to simplify the analytical workflow through the integration of extraction and enrichment. , In addition, SDME technique is ideally suited for coupling with fluorescence spectroscopy because the solvent used in SDME is transparent in the visible region and does not interfere with direct visual readout and spectral analysis. , In recent years, the integration of liquid-phase microextraction with non-instrumental optical detection has been reported. However, the attention was concentrated mainly on the direct detection of the analyte to be assayed. For example, Bendicho et al reported core–shell CdSe/ZnS QDs dispersed in the organic solvent droplet as a headspace SDME (HS-SDME) fluorescence detection probe for the selective detection of volatiles by combining microfluorescence spectroscopy .…”
Section: Introductionmentioning
confidence: 99%